Which strain of the avian coronavirus vaccine will become the prevalent one in China next? - Li, Haizhu; Liu, Gengsong; Zhou, Qiaoyan; Yang, Hongchun; Zhou, Congcong; Kong, Weili; Su, Jieyu; Li, Gonghe; Si, Hongbin; Ou, Changbo (Frontiers in Veterinary Science, 2023)
Infectious bronchitis virus (IBV) is a vital pathogen in poultry farms, which can induce respiratory, nephropathogenic, oviduct, proventriculus and intestinal diseases. Based on the phylogenetic classification of the full-length S1 gene, IBV isolates have been categorized into nine genotypes comprising 38 lineages. GI (GI-1, GI-2, GI-3, GI-4, GI-5, GI-6, GI-7, GI-13, GI-16, GI-18, GI-19, GI-22, GI-28, and GI-29), GVI-1, and GVII-1 have been reported in China in the past 60 years. In this review, a brief history of IBV in China is described, and the current epidemic strains and licensed IBV vaccine strains, as well as IBV prevention and control strategies, are highlighted. In addition, this article presents unique viewpoints and recommendations for a more effective management of IBV. The recombinant Newcastle Disease virus (NDV) vector vaccine expressed S gene of IBV QX-like and 4/91 strains may be the dominant vaccine strains against NDV and IBV.